Infrastructures de données géographiques et flux d’information environnementale - Matthieu Noucher (Netcom)
Spatial Data Infrastructure (SDI), that emerge at every scale since 1990, are plateform that gather datas, informatics network, norme and standard, organizational arrangement and human ressources in order to facilitate and coordinate spatial data sharing, management and access on a specific territory and/or thematic. The purpose of this article is to present the Spatial Data Infrastructure that appears today as an essential driver of institutional data diffusion. After presenting the concept and its inclusion in the actual legal and technologic context, an analysis of SDI as a sociotechnical system allows us to identify some issues related to the question of the production and management of knowledge on the environment. Then, we propose some markers to analyse spatial data patrimonies nowadays accessible and to analyse territorial and informational recomposition they translate. The aim is to make spatial data infrastructure not just a research tool but a real object of research for a better understanding of the flow of environmental information.